EFFECT OF ACTIVITY-BASED INSTRUCTIONAL METHOD ON SECONDARY SCHOOL STUDENTS' ACADEMIC ACHIEVEMENT IN ECOLOGICAL CONCEPTS IN ASABA EDUCATION ZONE (UNIZIK Journal of STM Education, 2024)
The study explored the effect of activity-based instructional method (ABIM) on secondary school students’ academic achievementin ecological concepts. The study is a quasi-experimental studyadopting the non-randomized control group design. 82 (39 males and 43 females) senior secondary year one (SS1) students drawn fromthe 6922 SS1 students in the zone, using multi-stage sampling procedure, constituted the sample size. The sampled students who were in two intact classes were randomly assigned to experimental and control groups using a flip of a coin. The instrument for data collection was an Ecology Achievement Test (ECAT), adapted by the researcher, from compiled biology past questions. ECATwas validated by three expertsand its reliability,which yielded 0.86 reliability coefficient,was that of internal consistency, established using Kuder-Richardson 20. Mean and standard deviation were used in answering the research questions while analysis of covariance (ANCOVA) was used to test the null hypotheses at 0.05 alpha levels. The findings of the study revealed that, irrespective of gender, ABIM enhanced students’ academic achievement in learning ecological concepts more than conventional lecture method. Also, there was no interaction effect of gender and teaching methods on students’ academic achievement in ecology. Based on the findings, the study concluded that ABIM is a gender friendly approach that enhances students' academic achievement in ecology and recommended among others that ABIM should be adopted by biology teachers in schools to improve students’ academic achievement in ecology.
Keywords: Academic Achievement, Activity-Based Instructional Method (ABIM), Ecology, Gender.